A Research Review of Common Memorial Sites, Connecting the Friendship between Turkey and Pakistan.: ترکی اور پاکستان کی دوستی کو مربوط کرنے والے مشترکہ یادگاری مقامات کا تحقیقی جائزہ (DARYAFT, 2022)
Monuments, schools, hospitals and named streets, parks or squares that are mutually constructed in big cities as examples of historical and cultural values are places of common memory in Turkey and Pakistan. Accurate understanding of the collective past and historical consciousness affects not only the present, but also the shaping of the future. Therefore, cultural phenomena such as tradition, language, and religion, national and religious holidays in the collective past of a society contribute to the formation of historical consciousness and national identity. The memory places, which play an important role in the construction of the common future through the cultural values of the Pakistani and Turkish societies, also reflect the socio-political and cultural memory objects of both societies. In this study, memory spaces that play an active role in the cultural interaction between Pakistan and Turkey will be discussed with the theory of memory space (lieu de mèmoire) of French historian Pierre Nora. In addition, how and what memory spaces that reflect the identity of a society symbolize in terms of both symbolic and historical reality will be examined.
Keywords: Turkey, Pakistan, Memory, Place of Memory, Cultural interaction, Tradition, Language, Religion, Identity